Factors That Promote and Inhibit Successful School-to-Work Transitions Among Engineering Students in India - Prasad Neriyanuri, Kalyana Rama (Global journal of Business and Integral Security, 2024)
Education plays a crucial role in enabling individuals to lead fulfilling lives while also supporting themselves financially. Within this context, successful transitions from school to the workforce are pivotal for personal, societal, and economic development. In India, engineering education holds particular significance due to its evolution over recent decades, playing a central role in the country's growth, modernization, and workforce development. This study represents a pioneering effort to identify the factors that promote or inhibit successful school-to-work transitions among engineering students in India. Through an exploratory research approach, combining survey data from engineering students of diverse backgrounds, interviews with training and placement officers, and a family member survey, this study aims to shed light on this critical issue. The study has explored two primary hypotheses: the significance of internships in facilitating successful transitions and the potential hindrance of solely academic excellence without exposure to market-relevant skills. The findings underscore the importance of collaboration between industry and academia to enhance school-to-work transitions. Key factors identified as promoting successful transitions include internships, market-relevant skills, soft skills, placement preparation, and networking. Conversely, factors inhibiting successful transitions include a sole focus on academic performance, failure to seek early support, lack of in-depth knowledge, neglect of priorities, and an inadequate understanding of one's strengths. This study contributes to the ongoing discourse on improving school-to-work transitions. It highlights the critical role of collaboration between stakeholders in fostering successful transitions for engineering students in India.